PROCEDURAL ESSAY WRITING: STUDENTS’ PROBLEMS AND STRATEGIES - Ambarwati, Septina; Listyani, Listyani (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
Language learners living in the expanding circle certainly face probems that may not be encountered by their counterparts in the inner or outer circle. One of the problems these learners face is in the field of writing. They also need special strategies in overcoming these problems. This study was done to investigate the problems faced by students in writing Procedural Essays as well as the strategies to overcome the problems. This study attempted to answer two research questions: What problems do students face in writing Procedural Essays? and What are students' strategies to overcome the problems in writing Procedural Essays? This study used a qualitative method. To collect the data, the researchers used two instruments, which are open-ended and close-ended questionnaires and interviews. The participants of this research were 27 students from batch 2020 who took Procedural Writing Class in the 2020/2021 Academic Year. The results of this research showed that there were three problems faced by students in writing Procedural Essays. Those problems were problems of topic development, problems with vocabulary, and problems with grammar. The result also indicated the most strategies used by students to overcome the problems, such as receiving feedback from teachers, making an outline, and asking friends for help.